DAMPAK LAYANAN INTERNET BANKING DALAM MENINGKATKAN KEPUASAN NASABAH - Noviryantika Noviryantika (STIE 'INDONESIA' Pontianak, 2019)
Internet banking is currently a method of providing banking services to its customers. PT. Bank Bukopin uses Internet Banking technology in an effort to provide satisfaction to its customers. The purpose of this study was to determine the effect of efficiency, fulfillment, system availability, privacy, responsiveness, compensation and contact on the quality of internet banking services on customer satisfaction. The independent variable is the quality of internet banking services using 7 variable dimensions, while the dependent variable is customer satisfaction. The data analysis method uses multiple regression. The results showed that efficiency, fulfillment, system availability, responsiveness and compensation on the quality of internet banking services had a positive and significant effect on customer satisfaction at PT. Bank Bukopin Pontianak Branch. While privacy and contacts on the quality of internet banking services have a negative and significant impact on customer satisfaction of PT. Bank Bukopin Pontianak Branch.